Potential of medicinal plants to ameliorate neovascularization activities in diabetes: A systematic review - Yong Phaik Har; New Shin Yee; Azzani Meram; Wu Yuan Seng; Chia Vi Vien; Ng Zhi Xiang (Endocrine Regulations)
Hyperglycemia in diabetes mediates the release of angiogenic factors, oxidative stress, hypoxia, and inflammation, which in turn stimulate angiogenesis. Excessive angiogenesis can cause diabetic retinopathy, diabetic neuropathy, and diabetic nephropathy. All of these complications are debilitating, which may lead to an increased susceptibility to lower-limb amputations due to ulcerations and infections. In addition, microvascular alterations, segmental demyelination, and endoneurial microangiopathy may cause progressive deterioration ultimately leading to kidney failure and permanent blindness. Some medicinal plants have potent anti-angiogenic, antioxidant or anti-inflammatory properties that can ameliorate angiogenesis in diabetes. The purpose of this systematic review is to demonstrate the potential of medicinal plants in ameliorating the neovascularization activities in diabetes. Manuscripts were searched from PubMed, Science Direct, and Scopus databases, and Google Scholar was used for searching additional papers. From 1862 manuscripts searched, 1854 were excluded based on inclusion and exclusion criteria and 8 were included into this systematic review, whereas the required information was extracted and summarized. All identified medicinal plants decreased the high blood glucose levels in diabetes, except the aqueous extract of Lonicerae japonicae flos (FJL) and Vasant Kusumakar Ras. They also increased the reduced body weight in diabetes, except the aqueous extract of FL and total lignans from Fructus arctii. However, methanolic extract of Tinospora cordifolia and Vasant Kusumakar Ras were not tested for their ability to affect the body weight. Besides, all medicinal plants identified in this systematic review decreased the vascular endothelial growth factor (VEGF) protein expression and vasculature activity demonstrated by histopathological examination indicating promising anti-angiogenic properties. All medicinal plants identified in this systematic review have a potential to ameliorate neovascularization activities in diabetes by targeting the mechanistic pathways related to oxidative stress, inflammation, and angiogenesis.